2015
DOI: 10.1039/c4ra13408g
|View full text |Cite
|
Sign up to set email alerts
|

Mussel inspired preparation of highly dispersible and biocompatible carbon nanotubes

Abstract: A novel method for preparation of water dispersible and biocompatible carbon nanotubes via mussel inspired PEGylation has been developed for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…As compared with the pristine CNTs, the funcitonalized CNTs have demonstrated to be better performance in heavy metal ion removal [17,18]. Previously, a number of surface modification strategies such as surface oxidation with concentrated acid, non-covalent with surfactants and amphiphilic polymers, in situ polymerization and hybridized with inorganic nanomaterials have been reported [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. On the other hand, different physical methods such as plasma irradiation and gamma-irradiation have also developed for surface modification of CNTs.…”
Section: Introductionmentioning
confidence: 97%
“…As compared with the pristine CNTs, the funcitonalized CNTs have demonstrated to be better performance in heavy metal ion removal [17,18]. Previously, a number of surface modification strategies such as surface oxidation with concentrated acid, non-covalent with surfactants and amphiphilic polymers, in situ polymerization and hybridized with inorganic nanomaterials have been reported [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. On the other hand, different physical methods such as plasma irradiation and gamma-irradiation have also developed for surface modification of CNTs.…”
Section: Introductionmentioning
confidence: 97%
“…It is well-known that the selfpolymerization of dopamine can coat on a large number of material surfaces for the adhesion of PDA. More importantly, the PDA coatings can provide an active platform for further surface modification through different strategies including surface initiated polymerization, free radical polymerization, and Michael addition reaction [42][43][44][45][46][47][48]. In this work, the PSPSH polymer terminated with amino group was first synthesized via free radical polymerization using cysteamine hydrochloride as the chain transfer agent and SPSH as the monomer.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Lu et al have demonstrated that PDA nanospheres can be heated by near infared (NIR) laser and exhibited better photothermal effect than that of gold nanoparticles [65]. On the other hand, our recent report suggested that surface modification of carbon nanotubes with PDA and PEG can obviously improve the dispersibility and biocompatibility of carbon nanotubes [76]. The possible mechanism for enhanced biocompatibility is partly due to the PEG coating and the free radical scavenging capability of PDA coating.…”
Section: Preparation Of Sio 2 -Pda-poly(pegma-co-napam)mentioning
confidence: 95%